Interpreting patterns of ecoenzymatic stoichiometry - Moorhead, Daryl; Cui, Yongxing; Sinsabaugh, Robert; Schimel, Joshua (Soil biology & biochemistry, 2023)
The stoichiometry of extracellular enzyme activities has been both proposed and refuted to quantify resource use efficiency and resource limitations to soil microbial communities. The approach evaluates the acquisition of resources obtained through the enzyme-mediated catalysis of polymeric substrates. However, labile resources that do not require enzyme activity circumvent this catalytic pathway, can alter the balance of enzyme activities and skew their interpretation. More specifically, the microbial use of soluble resources can occur within minutes to hours of their addition whereas the use of polymeric resources depends on the production and turnover of extracellular enzymes (days to weeks). This temporal difference between potential, short-term microbial metabolic responses to soluble resources and longer-term community responses to enzyme-mediated acquisition of polymeric resources can produce seemingly conflicting interpretations of microbial resource limitations. However, stoichiometric tools provide insights to microbial resource use and limitations that differ in functional context from other measures of microbial community behavior. •Enzyme stoichiometry quantifies microbial resource acquisition from polymeric sources.•Soil enzyme activities reflect long-term microbial resource acquisition strategies.•Microbes can acquire simple, soluble resources independent of enzyme activity.•Limitations in one type of critical resource can alter microbial demands for others.